The impact of the oxidising agent type and coagulant type on the effectiveness of coagulation in the removal of pollutants from underground water with an increased content of organic substances - Krupińska, Izabela (Journal of Environmental Engineering and Landscape Management, 2016)
The article presents the results of studies concerning the impact of the method of Fe(II) ion oxidisation on the effectiveness of coagulation in the removal of pollutants from underground water with an increased content of organic substances (TOC up to 5.338mgC/dm3). In order to oxidise the Fe (II) ions before the coagulation process, the underground water was subjected to aeration, or either potassium manganate (VII) or hydrogen peroxide were dosed in the stoichiometric amount in view of the concentration of Fe (II). The efficiencies of three coagulants were compared: that of aluminium sulphate (VI), polyaluminium chloride (PAX XL-60) and iron (III) sulphate (VI) – PIX-112. Coagulant doses expressed in mgal/dm3 or mgfe/dm3 and changed within the range of 1 to 6 mgal(Fe)/dm3. Volume coagulation was performed in 1-dm3 groundwater samples using 1-minute rapid mix (250 rpm) and 25-minute slow mix (30 rpm) followed by 2-hour sedimentation. It has been proven that the type of oxidising agent and coagulant, as well as their dose, co-determines the effectiveness of the removal of the pollutants. Among the used methods of iron (II) oxidisation, the best effects have been achieved by potassium manganate (VII) with regards to the effects of the reduction of colour, turbidity, concentration of manganese and organic substances, and with regards to the extent of total iron removal, oxidisation with dissolved oxygen was the most effective solution. Hydrogen peroxide was the least useful oxidising agent. Regardless of the oxidising agent the best results in the removal of pollutants in the coagulation process were produced by the coagulant: pre-hydrolysed polyaluminium chloride PAX XL-60, and the worst by the iron coagulant: iron (III) sulphate (VI). Analysis of the results of the studies also showed that the effectiveness of pollutant removal from the underground water in the coagulation process was decreased together with an increase in the value of the TOC/Fetot only in the case of water samples which, after aeration, differed in terms of the coefficient of organic substances and total iron (D). Such a relationship was not found when potassium manganate (VII) and hydrogen peroxide were used for oxidisation before the coagulation process.